2012
DOI: 10.1016/j.jsp.2011.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Do girls and boys perceive themselves as equally engaged in school? The results of an international study from 12 countries

Abstract: This study examined gender differences in student engagement and academic performance in school. Participants included 3420 students (7th, 8th, and 9th graders) from Austria, Canada, China, Cyprus, Estonia, Greece, Malta, Portugal, Romania, South Korea, the United Kingdom, and the United States. The results indicated that, compared to boys, girls reported higher levels of engagement in school and were rated higher by their teachers in academic performance. Student engagement accounted for gender differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
186
2
55

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(266 citation statements)
references
References 72 publications
23
186
2
55
Order By: Relevance
“…These studies highlighted the validity of the phenomenon across international contexts. Regarding the influence of background variables internationally, some studies find gender to be significant (e.g., Ma, 2003;Lam et al, 2012), but others do not (Cemalcilar, 2010;OECD, 2013). Regarding age, studies show that students' sense of belonging often decreases after the transition from primary school to secondary level (e.g., Gillen-O'Neel & Fuligni, 2013;Lester et al, 2013).…”
Section: School Belonging As a Sense Of Membershipmentioning
confidence: 99%
“…These studies highlighted the validity of the phenomenon across international contexts. Regarding the influence of background variables internationally, some studies find gender to be significant (e.g., Ma, 2003;Lam et al, 2012), but others do not (Cemalcilar, 2010;OECD, 2013). Regarding age, studies show that students' sense of belonging often decreases after the transition from primary school to secondary level (e.g., Gillen-O'Neel & Fuligni, 2013;Lester et al, 2013).…”
Section: School Belonging As a Sense Of Membershipmentioning
confidence: 99%
“…Some researchers purport engagement should be viewed as a three-part typology that includes behavioral, emotional, and cognitive aspects (Fredericks, Blumenfield, & Paris, 2004;Jimerson, Campos, & Grief, 2003;Lam et al, 2012;Marx, Simonsen, & Kitchel, 2016;Sinclair, Christenson, Lehr, & Anderson, 2003). A multidimensional view of the engagement construct (Appleton et al, 2008;Appleton et al, 2006) highlights its complexity as it is often regarded as a meta-construct (Axelson & Flick, 2011;Jimerson et al, 2003;Lam et al, 2012;Sinclair et al, 2003).…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…A multidimensional view of the engagement construct (Appleton et al, 2008;Appleton et al, 2006) highlights its complexity as it is often regarded as a meta-construct (Axelson & Flick, 2011;Jimerson et al, 2003;Lam et al, 2012;Sinclair et al, 2003). Specifically, Fredericks et al (2004) identified three dimensions of student engagement that included behavioral, emotional, and cognitive factors; a conceptualization echoed by Marx, et al (2016) in their examination of student course engagement.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Even if the neoliberal educational discourse is focused on individuals and rarely points out categories of students, it is a common phenomenon in most countries that boys are increasingly represented as losers in the school system (see, e.g., Hinnerich, Höglin, & Johannesson, 2011;Lam et al, 2012;Lucey, Walkerdine, 1999, Watson, 2011Younger & Warrington, 2008). This is the topic of three programs ( in favor of actions directed at the future (Ball, 2003;Oria et al, 2007).…”
Section: Gender Class and Placementioning
confidence: 99%